Study on leader personality and leadership style among telecommunication project managers in Malaysia - Shao Qin, Yan (2014)
This research was conducted to identify the relationship between the 16 Personality Global Factors and the leadership style among telecommunications project managers in Malaysia. There are five personality studies in this research which are the extraversion, anxiety, tough-mindedness, independence, and self-control. There are three types of leadership style study in this research which included the task-oriented leadership, change-oriented leadership and relations-oriented leadership. Two sets of questionnaires were developed and distributed to the managers and their subordinates respectively. A total sample of 31 managers and 31 subordinates were used in this study. The results of this study showed that extraversion, anxiety, and independence personality are positively correlated with the change-oriented leadership, while tough-mindedness and self-control have negative relationships towards the change-oriented leadership. Besides that, task-oriented leadership is positively associated with tough-mindedness, independence and self-control, while it is negatively associated with extraversion and anxiety. Extraversion, and tough-mindedness personality are positively correlated to the relations-oriented leadership compared to the anxiety personality which is negatively correlated with